2008
DOI: 10.4049/jimmunol.180.10.6457
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Central Nervous System Plasmacytoid Dendritic Cells Regulate the Severity of Relapsing Experimental Autoimmune Encephalomyelitis

Abstract: Plasmacytoid dendritic cells (pDCs) have both stimulatory and regulatory effects on T cells. pDCs are a major CNS-infiltrating dendritic cell population during experimental autoimmune encephalomyelitis but, unlike myeloid dendritic cells, have a minor role in T cell activation and epitope spreading. We show that depletion of pDCs during either the acute or relapse phases of experimental autoimmune encephalomyelitis resulted in exacerbation of disease severity. pDC depletion significantly enhanced CNS but not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
128
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 27 publications
8
128
0
2
Order By: Relevance
“…1). Previous studies, using severalfold higher doses of anti-PDCA1 mAb, have demonstrated that pDC numbers are normalized 3-5 days following anti-PDCA1 treatment [18,20]. The incidence of EAE was 62% and the maximum mean EAE score of 1.270.4 (po0.05) for anti-PDCA1-treated mice, compared with 92% incidence and a maximum mean EAE score of 2.870.5 for normal IgG-treated mice ( Fig.…”
Section: Results Pdc Promote Eaementioning
confidence: 92%
See 1 more Smart Citation
“…1). Previous studies, using severalfold higher doses of anti-PDCA1 mAb, have demonstrated that pDC numbers are normalized 3-5 days following anti-PDCA1 treatment [18,20]. The incidence of EAE was 62% and the maximum mean EAE score of 1.270.4 (po0.05) for anti-PDCA1-treated mice, compared with 92% incidence and a maximum mean EAE score of 2.870.5 for normal IgG-treated mice ( Fig.…”
Section: Results Pdc Promote Eaementioning
confidence: 92%
“…Thus, we could not observe any influence of pDC on ICOS signaling in T cells in our system. In a recent study, the clinical signs of EAE exacerbated considerably if pDC were depleted during the peak of the disease process [18]. To reproduce the results of this study in MOGimmunized C57BL/6 mice, we depleted pDC 8 days after immunization and then every other day for a total of four treatments (Fig.…”
Section: Icos Signaling In T Cells Is Not Affected By the Pdc Depletionmentioning
confidence: 99%
“…In experimental autoimmune encephalomyelitis, an animal model of human MS, a critical tolerogenic effect of pDCs was demonstrated (14). Unlike myeloid DCs, pDCs had only a minor role in T cell activation and epitope spreading, but negatively regulated pathogenic CNS CD4 + T cell responses, suggesting a regulatory role during experimental neuroinflammation (14). However, it has to be noted critically that the exact mechanism of pDC accumulation and their role during CNS inflammation are not well understood.…”
mentioning
confidence: 99%
“…Active recruitment of pDCs into the CNS and their accumulation in white matter lesions and leptomeninges of MS brains has also been demonstrated (13). In experimental autoimmune encephalomyelitis, an animal model of human MS, a critical tolerogenic effect of pDCs was demonstrated (14). Unlike myeloid DCs, pDCs had only a minor role in T cell activation and epitope spreading, but negatively regulated pathogenic CNS CD4 + T cell responses, suggesting a regulatory role during experimental neuroinflammation (14).…”
mentioning
confidence: 99%
“…pDCs were found to limit the differentiation of effector Th1 and Th17 cells in the EAE model in an indoleamine 2,3-dioxygenase (IDO)-dependent manner; these effects are not associated with the differentiation of FoxP3 þ Tregs. 55 Taken together, these data show that, both in the periphery and the CNS, DCs control the balance between effector and regulatory T cells and consequently the development of autoimmune disorders.…”
Section: Role Of Dcs In the Peripheral Activation Of T Cellsmentioning
confidence: 80%